Manajemen Program Permainan Bowling untuk Mengembangkan Kemampuan Literasi Numerik pada Anak Usia Dini di TK pertiwi 1 Dukuhwaluh - Siti Nurjanah; Novan Ardy Wiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the management of the bowling game program in developing early childhood numeracy literacy skills at TK Pertiwi 1 Dukuhwaluh. This research uses a qualitative approach with data collection techniques including observation, interviews, and documentation. The results showed that the bowling game program was implemented through well-structured planning, collaborative organization, meaningful and enjoyable implementation, and continuous program control based on the principle of continuous improvement. Children showed improvement in recognizing numbers, counting, and making simple quantity comparisons. The conclusion is that the bowling game can be an effective strategy in early childhood numeracy learning. Keywords: bowling game, early childhood, numeracy literacy, learning management